2020
DOI: 10.1149/1945-7111/ab8976
|View full text |Cite
|
Sign up to set email alerts
|

4-Electrode Full Cells for Operando Li+ Activity Measurements and Prevention of Li Deposition in Li-Ion Cells

Abstract: Li plating is a severe and safety relevant aging mechanism which has to be avoided. A new 4-electrode operando pouch full cell, with two Li reference electrodes is developed. The voltage shifts between the two Li metal electrodes are correlating directly with changes in the Li+ activity a[Li+] in the electrolyte in front of the anode surface. We take advantage of the Li+ activity dependency of the Li+/Li redox potential as described by the Nernst equation to measure the Li+ activity in the electrolyte. On this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 55 publications
(144 reference statements)
0
13
0
Order By: Relevance
“…[ 98 ] The increase of the diffusion barrier of Li + in graphite with SOC is unfavorable for the fast‐charging capability since it leads to a higher probability of Li metal deposition for high SOCs. [ 102–105 ]…”
Section: Anodementioning
confidence: 99%
See 4 more Smart Citations
“…[ 98 ] The increase of the diffusion barrier of Li + in graphite with SOC is unfavorable for the fast‐charging capability since it leads to a higher probability of Li metal deposition for high SOCs. [ 102–105 ]…”
Section: Anodementioning
confidence: 99%
“…[ 170 ] Consistent with this, post‐mortem analysis after cycling showed that lithium metal is mostly deposited on the anode surface. [ 173–175 ] The anode potential and therefore the tendency of lithium metal deposition is affected by electrolyte additives, [ 176 ] anode active materials, [ 177 ] the anode coating thickness, [ 38 ] operating parameters such as temperature, C‐rate, and SOC [ 38,103–105,177 ] as well as the ratio of the areal capacities between anode and cathode (N/P ratio). [ 19,178–181 ]…”
Section: Anodementioning
confidence: 99%
See 3 more Smart Citations